Adapting management to a changing world: Warm temperatures, dry soil, and interannual variability limit restoration success of a dominant woody shrub in temperate drylands. (20th July 2018) - Shriver, Robert K.; Andrews, Caitlin M.; Pilliod, David S.; Arkle, Robert S.; Welty, Justin L.; Germino, Matthew J.; Duniway, Michael C.; Pyke, David A.; Bradford, John B.
Abstract: Restoration and rehabilitation of native vegetation in dryland ecosystems, which encompass over 40% of terrestrial ecosystems, is a common challenge that continues to grow as wildfire and biological invasions transform dryland plant communities. The difficulty in part stems from low and variable precipitation, combined with limited understanding about how weather conditions influence restoration outcomes, and increasing recognition that one‐time seeding approaches can fail if they do not occur during appropriate plant establishment conditions. The sagebrush biome, which once covered over 620, 000 km 2 of western North America, is a prime example of a pressing dryland restoration challenge for which restoration success has been variable. We analyzed field data on Artemisia tridentata (big sagebrush) restoration collected at 771 plots in 177 wildfire sites across its western range, and used process‐based ecohydrological modeling to identify factors leading to its establishment. Our results indicate big sagebrush occurrence is most strongly associated with relatively cool temperatures and wet soils in the first spring after seeding. In particular, the amount of winter snowpack, but not total precipitation, helped explain the availability of spring soil moisture and restoration success. We also find considerable interannual variability in the probability of sagebrush establishment. Adaptive management strategies that target seeding during cool, wet years or mitigate effects of variability through repeated seeding may improve the likelihood of successful restoration in dryland ecosystems. Given consistent projections of increasing temperatures, declining snowpack, and increasing weather variability throughout midlatitude drylands, weather‐centric adaptive management approaches to restoration will be increasingly important for dryland restoration success. Abstract : Restoration of native vegetation in dryland ecosystems, which encompass over 40% of terrestrial ecosystems, is a persistent and growing challenge. The sagebrush biome is a prime example of a pressing dryland restoration challenge for which success has been variable. Our results indicate big sagebrush occurrence after wildfire and seeding is most strongly associated with cool temperatures and wet soils, driven by abundant snowpack, in the first growing season. Adaptive management strategies that target seeding during cool, wet years, or mitigate effects of variability through repeated seeding may improve restoration outcomes in dryland ecosystems in the face of changing climate.